Marathon running: the physiological and pathological effects with particular reference to renal function and fluid shifts - Irving, Robert Anthony (Department of Medicine, 2026)
Marathon running can induce acute renal failure and hyponatraemia and may be associa~ed with the formation o f renal stones. The pathogenesis o f these conditions is uncertain and the physiological =esponse with regard to renal function and fluid shifts 2as not been clearly defined, particularly during the r ecovery days after mara thon running. In t his thesis, eight marathon races were studied and da i ly blood and 24 hour urine samples ~ere collected. The fo llowing were measured or calc~: ated: urine output, creatinine, osmolal, free water =nd renal beta2- microglobulin clearances as well as total protein, sodiu::i., potassium, urea and creatinine e xcretion rates. Changes in total serum contents of sodium, =h loride, albumin, total protein and uric acid, and in p l ~sma volume and mean cell volume, were calculated. Plasma c -reactive protein concentrations, aspartate transc.::i nase, lactate dehydrogenase and creatine kinase activities were also measured. VI Urine samples from runners who participated in a further 2 marathons were subjected to parti cle counting, while deposited crystals were examinec #ith a scanning electron mircroscope and X-ray powder diffraction. Eight runners who developed hyponatraemia after an 88km marathon were studied during recovery, for fluid and sodium balance and renal function. The principal finding was that contrary to traditional belief, renal function as measured by urine output, creatinine, osmolal and free-water clearance, urea and creatinine excretion and production is generally well maintained. Plasma volume was maintained during a 56km marathon due to intravascular protein and sodium influxes, while a decreased urine sodium excretion occurred for at least 24 hours after the race. Urine beta2-microglobulin excretion and plasma beta2- microglobulin concentration increased but renal tubular impairment was not generally found. During the post-race days there was an increase in creatinine clearance as well as a plasma volume expansion (of up to 12.5%) due to an intravascular influx of albumin (17g on Day 1) and an increased plasma content of sodium. Two of the total of 27 runners studied developed temporary renal tubular dysfunction; one was clearly related to an inadequate fluid intake. VII The crystalluria found in runners was identical to that of. recurrent stone formers. Crystalline particles were mainly calcium oxalate dihydrate with crystal aggregation and numerous crystals in the 15-40 um diameter range. Thus runners are at risk of stone formation. VIII Finally, it was shown that the hyponatraemia of exercise was caused by fluid overload (between 1.2 and 5.9L), with only moderate sodium loss. The subjects' plasma volumes were markedly decreased (up to 24%). During the recovery period both creatinine clearance and urine output were elevated.